Mongolia : : a centrally planned economy in transition.. - Rana, Pradumna Bickram( 1947-); Asian Development Bank. (New York: Oxford University Press, 1992)
Growing disenchantment with the socialist economic model, the breakdown of the Council for Mutual Economic Assistance bloc, and the advent of perestroika and glasnost in the former Soviet Union and Eastern Europe, form the basis for Mongolia's decision to open its economy and implement a range of economic reforms. In its current effort towards structural change, Mongolia's government has adopted a comprehensive series of reforms aimed at dismantling the central planning system and establishing a market-based economy. The process started in 1986 and gained momentum with the 1990 election of a new government.
Mongolia: A Centrally Planned Economy in Transition is based mainly on the findings of the Asian Development Bank's first economic mission to Mongolia. The study begins with a comprehensive review and analysis of Mongolia's economy over several decades. It then focuses on the economic reforms undertaken since the mid-1980s to transform the economy from a centrally planned system to a market-driven system. Detailed time series data on economic and social indicators are included.
Natural Resource Base. Pattern of Economic Development and Its Impact on the Environment. Issues. Agenda for Action.
"P.B. Rana revised the Report and was also responsible for the production of this book"--Pref.
Rev. ed. of: Economic report on the Mongolian People's Republic / K.H. Moinuddin ... et al.
"Published for the Asian Development Bank."
Keywords: Wirtschaftsreform; Economische hervormingen; Mongolia -- -- Economic conditions; Mongolia -- -- Economic policy; Mongolei; Economic conditions -- Policies -- Of -- Government; Mongolia